Effect of 10 Week Strength Training on Nicotinic Acetylcholine Receptor Rate in Fast and Slow Twitch Skeletal Muscles of Rats - AH Parnow; Z Gourgin-e-Karaji; R Gharakhanlou; S Rajabi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2012)
Introduction: This study aimed at determining the impact of strength training on the rate of Nicotinic Acetylcholine Receptor(nAChR) at fast and slow twitch skeletal muscles of rats. Methods: Ten Wistar rats were divided into two groups randomly: control group(n=5) and strength-training group(n=5) which the latter group participated in a 10-week strength-training program. The strength training program consisted of climbing a 1-meter–long ladder set at 85° angle, with a weight attached to the rats’ tails. The attached weight was gradually increased from 35 g during the first session, to 600 g at the last session of the training program. Forty-eight hours after 10-week training, animals were anaesthetized with a mixture of Ketamine TM and Xylazine and the soleus and anterior tibialis were removed under sterile condition. After removal, tissues were quickly frizzed in liquid nitrogen and then were kept at -70 ° C for later usage. For nAChR assay, ELISA kit(Accurate Chemical, USA) was utilized. Results: The study results revealed that there was a significant difference between control and strength training groups in nAChR rate in both slow and fast twitch muscle (respectively, P= 0.00 and P=0.03 ). The results also showed that there was a significant difference among fast and slow twitch muscle’s nAChRs in strength(P=0.02), though such difference was not observed in control group(P= 0.07). Conclusion: Regarding significant increase of nAChR in both slow and fast twitch muscles following strength training, strength training seems to play a crucial role in increase of nAChR in fast and slow twitch muscle through neurotrophic factors that contribute to synthesis and clustering of nAChR.